Can interprofessional research enhance health care students' understanding and knowledge towards evidence based practice: A cross sectional study. (September 2022) - Hemingway, Steve; Roberts, Peter; Stead, Joanne; Stephenson, John; Lui, Steve
Abstract: Aim: To explore how inter-professional collaboration in the teaching and learning of research skills prepares undergraduate students for their professional roles in healthcare via an evaluation of inter-professional research modules from the student perspective. Participants and settings: Participants were selected from a university in the North of England where all undergraduate Healthcare students were taught Research and Evidence Based Practice (EBP) through interprofessional education (n = 400). Methods: Quantitative data was collected using an adapted Attitudes Towards Interprofessional Education Scale and internally-designed pilot instruments. Qualitative data was also collected via open comment to evaluate the taught research module. Results: 50 students completed the survey pre-module and 49 students completed the survey post-module. The participants' views towards inter-professional education (IPE) are generally positive: the median responses of 4 single-item measures assessing inter-professional learning on 7-point Likert scales were 5 or above (where higher scores represented more positive perceptions). Scores on the Attitudes towards Interprofessional Education scale also generally represented positive opinions, with a mean post-test score of 58.8 on a scale from 5 to 75, with higher scores indicating greater levels of positivity. No evidence for a statistically significant improvement from the pre- to post- 3rd year experience of the IPE/research theme was revealed. Qualitative data identified six themes: promoting team working, developing awareness of other health care professional's roles, polarising research and practice, multidisciplinary team (MDT) working or not working, logistical issues and developing research skills. Conclusions: This study raised questions about the appropriateness of "unnatural" pairings for undertaking research projects. Whilst the students valued working together in the research process, they do not appear to have perceived a universal benefit to their inter-professional clinical practice.